Konstitucija ternarnega sistema Al-Ti-B v aluminijevem kotu - Zupanič, Franc (Kovine zlitine tehnologije, 1999)
In this work the Al-corner of the ternary system Al-Ti-B was sistematically investigated. Several alloys with cumulative content of titanium and boron with 0,1 , 0,5 and 1 weight percentage Ti+B were prepared. Differential thermal analysis (DTA) of all alloys were carried out to determine the liquidus temperatures and temperatures of uni- and invariant reactions. Microstructure of all alloys was analysed by different techniques of metallographic analysis (light and scanning electron microscopy, EDS and X-ray diffraction) in the as-cast condition and after DTA. By taking into account results of DTA, metallographic analysis and also the already known characteristic of Al-Ti-B alloys we analysed conditions in which uni- and invariant reactions are taking place. We also determined the nature of these reactions and proposed the most probable liquidus projection in the aluminium corner of the system Al-Ti-B.
Keywords: titan; večfazni sistemi; ternarni sistemi; zlitine; aluminij; Aluminij Mostar; aluminum; bor